Behavioral and Ovipositional Response of Diaeretiella rapae (Hymenoptera: Braconidae) to Rhopalosiphum padi and Brevicoryne brassicae in Winter Wheat and Winter Canola. Issue 6 (12th October 2018) - Ferguson, Mary E; Giles, Kristopher L; Elliott, Norman C; Payton, Mark E; Royer, Tom A
Abstract: Winter canola Brassica napus L. (Brassicales: Brassicaceae) was introduced to U.S. Southern Great Plains (Kansas, Oklahoma, Texas) growers to manage some difficult-to-control grassy weeds in winter wheat Triticum aestivum L. (Poales: Poaceae). Two braconid parasitoids, Diaeretiella rapae (M'Intosh) and Lysiphlebus testaceipes (Cresson) (Hymenoptera: Braconidae) are active in this cropping landscape. Both wasps move between crops but D. rapa e has a limited ability to develop in the main wheat aphid hosts, so L. testaceipes could influence D. rapae 's ability to maintain itself when canola is absent in the landscape. We compared behavioral responses of naturally emerged D. rapae and wasps that were excised before emergence to odor volatiles of host plant, aphid host and aphid-infested plants using two plant/aphid combinations (wheat/ Rhopalosiphum padi (L.) and canola/ Brevocoryne brassicae L. (Hemiptera: Aphididae). We also compared parasitism rates of D. rapae that were naturally emerged and excised from R. padi or B. brassicae on subsequent parasitism rates of R. padi or B. brassicae hosts. Naturally emerged wasps responded more strongly to host plant and host plant + aphid odors compared to excised wasps regardless of the host origin. Neither wasp group responded to odors from aphids alone. Both wasp groups were most attracted to odors from aphid-infested host plants, regardless of the combination. D. rapae parasitism rates on canola-reared aphids were higher than on wheat-reared aphids. D. rapae parasitism rates were lower when switched from its original host to the alternate host. Results suggest that D. rapae faces challenges to maintain significant populations in the wheat/canola landscape of the Southern Great Plains, especially in years when canola is not locally present.